Exploring Political Legacies - Farrall, Stephen. author. aut Link
XV, 107 p. 4 illus., 1 illus. in color.
Keywords: The concept of the political legacy, despite its importance for institutionalist and historically-minded political analysts more generally, remains both elusive and undeveloped theoretically. This book seeks to address that oversight by building on existing studies which have approached the notion of a legacy to offer a clear definition and operationalisation of the term which might be used to inform future research. Legacies we view as traces of the past in the present; the claim to the existence of a legacy is both a causal and a counter-factual claim. We propose, in the light of this, a multi-dimensional approach to gauging political legacies, reflecting on some of the theoretical, analytical and methodological concerns which need to be addressed in establishing credible claims to their existence. These we develop and illustrate with respect to the literature on Thatcherism. Stephen Farrall is Research Chair in Criminology in the Department of Criminology inthe College of Business, Law and the Social Sciences at the University of Derby, UK. He has held posts at the Universities of Oxford, Keele and Sheffield. Colin Hay is Professor of Political Science (Professeur des Universités) in the Centre d’études européennes and Director of Doctoral School in Political Science at Sciences Po, Paris, France. He is Professor of Political Analysis in the Department of Politics at the University of Sheffield, UK and founding co-Director of the Sheffield Political Economy Research Institute (SPERI). Emily Gray is a Senior Lecturer in Criminology at the University of Derby, UK. She has held research posts at the Universities of Edinburgh, Oxford, Keele and Sheffield.